Characterization of an Aldehyde Oxidoreductase From the Mesophilic Bacterium Aromatoleum aromaticum EbN1, a Member of a New Subfamily of Tungsten-Containing Enzymes - Arndt, Fabian; Schmitt, Georg; Winiarska, Agnieszka; Saft, Martin; Seubert, Andreas; Kahnt, Jörg; Heider, Johann (Frontiers in Microbiology, 2019)
The biochemical properties of a new tungsten-containing aldehyde oxidoreductase from the mesophilic betaproteobacterium Aromatoleum aromaticum EbN1 (AORAa) are presented in this study. The enzyme was purified from phenylalanine-grown cells of an overexpressing mutant lacking the gene for an aldehyde dehydrogenase normally involved in anaerobic phenylalanine degradation. AORAa catalyzes the oxidation of a broad variety of aldehydes to the respective acids with either viologen dyes or NAD+ as electron acceptors. In contrast to previously known AORs, AORAa is a heterohexameric protein consisting of three different subunits, a large subunit containing the W-cofactor and an Fe-S cluster, a small subunit containing four Fe-S clusters, and a medium subunit containing an FAD cofactor. The presence of the expected cofactors have been confirmed by elemental analysis and spectrophotometric methods. AORAa has a pH optimum of 8.0, a temperature optimum of 40°C and is completely inactive at 50°C. Compared to archaeal AORs, AORAa is remarkably resistant against exposure to air, exhibiting a half-life time of 1 h as purified enzyme and being completely unaffected in cell extracts. Kinetic parameters of AORAa have been obtained for the oxidation of one aliphatic and two aromatic aldehydes, resulting in about twofold higher kcat values with benzyl viologen than with NAD+ as electron acceptor. Finally, we obtained evidence that AORAa is also catalyzing the reverse reaction, reduction of benzoate to benzaldehyde, albeit at very low rates and under conditions strongly favoring acid reduction, e.g., low pH and using Ti(III) citrate as electron donor of very low redox potential. AORAa appears to be a prototype of a new subfamily of bacterial AOR-like tungsten-enzymes, which differ from the previously known archaeal AORs mostly by their multi-subunit composition, their low sensitivity against oxygen, and the ability to use NAD+ as electron acceptor.